2022
DOI: 10.1021/acsaom.2c00088
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Emissivity of Self-Assembled Magnetoresponsive Janus Particle Chain Suspensions

Abstract: Suspensions of magnetoresponsive Janus colloids form chains and undergo alignment under the influence of a magnetic field. When the magnetic field is aligned with a light path, light transmission through the sample increases as compared to randomly or orthogonally oriented chains. This study investigates the emissivity response of this suspension as a function of particle concentration and magnetic field strength. A variation of the Beer–Lambert model and ray-tracing simulations capture the behavior of the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…in the following we demonstrate the utility of the method through incorporation in a visually tangible application, as an alternative to E-ink displays. 36 In previous work by Gao et al , 45 it was shown that chains of ferromagnetic Janus particles can be rotated in a magnetic field giving rise to an optical dynamic range based on variable transmission of light. Others have shown similar, irreversible control of transmission through magnetic particles.…”
Section: Resultsmentioning
confidence: 99%
“…in the following we demonstrate the utility of the method through incorporation in a visually tangible application, as an alternative to E-ink displays. 36 In previous work by Gao et al , 45 it was shown that chains of ferromagnetic Janus particles can be rotated in a magnetic field giving rise to an optical dynamic range based on variable transmission of light. Others have shown similar, irreversible control of transmission through magnetic particles.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the utility of this synthetic method to general applications, we can utilize one of the inherent properties of Janus particle suspensions, as shown previously by Gao et al 47 Janus particle suspensions show an optical dynamic range, depending on their orientation and degree of chaining. Among the many possible applications discussed in the Introduction , one which is particularly applicable to this observation is magnetically actuated display materials.…”
Section: Resultsmentioning
confidence: 99%